PENERAPAN MANAJEMEN RISIKO PADA ASPEK PENANGANAN PRODUKSI (MAKE) DI PABRIK PENGALENGAN GUDEG YOGYAKARTA - ARSYAD SUMANTIKA (JURNAL ILMIAH SIMANTEK, 2020)
Gudeg Canning is one of the fast growing strategic industries in Yogyakarta. Smoothness in the supply chain canning activityis important. However, in the supply chain process, it was found that there were some risks that resulted in the system beingunable to run smoothly, for example due to engine failure, worker error, and failure / stopping of the supply chain, whichcaused downtime in the supply chain management. Supply Chain Operation Reference (SCOR) is a company activityconsisting of Plan, Source, Make, Deliver, Return, and Enable. In this study, supply chain risk management criteria arelimited to the aspects of production handling (Make), while the object of this study includes the Mrs. Tjitro, Gudeg, Bu Lies,and Bagong canning factories. The purpose of this study is to identify the risks that often occur in the handling of production(make) gudeg canning factory in Yogyakarta, determine the priority of risks that occur in the handling of production of warmcanneries in Yogyakarta, and provide risk management proposals. Risk assessment uses the Failure Mode and EffectAnalysis (FMEA) method, whereas for the proposed risk management uses the Root Cause Analysis (RCA) method. Therisk management proposal is based on the RPN's top five ranking. The results showed that more risks occur in the processof human resource management, failure (downtime) of the machine, capacity is not in accordance with the plan, idle timeoccurs because the production process stops or raw materials are lacking or other causes, and the production results are notas expected. Therefore, the proposed risk management of production handling increases the discipline, behavior and skills ofworkers, improves preventive maintenance to anticipate engine breakdowns, upgrades machines so that machineproductivity capabilities increase, increases collaboration in accessing shared information such as information sharing andcollaborative planning, and increases inventory management through safety stock and order policy.